Asset pricing with uncertain betas: A long-term perspective - Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2013)
How should one evaluate investment projects whose CCAPM betas are uncertain? This question is particularly crucial for projects yielding long-lasting impacts on the economy, as is the case for example for many green investments. We define the notion of a certainty equivalent beta. We show that its term structure is not constant and that, for short maturities, it equals the expected beta. If the expected beta is larger than a threshold (which is negative and large in absolute value in all realistic calibrations), the term structure of the certainty equivalent beta is increasing and tends to its largest plausible value. If current beliefs concerning the asset's beta are represented by a normal distribution, the certainty equivalent beta becomes infinite for finite maturities.
Keywords: G11; G12; E43; Q54; 330; asset prices; term structure; risk premium; certainty equivalent beta; Projektbewertung; Capital Asset Pricing Model; Laufzeit; Beta-Faktor; Risikoprämie; Zinsstruktur; Theorie